Cascading effects of defaunation on the coexistence of two specialized insect seed predators. (10th October 2016) - Peguero, Guille; Muller‐Landau, Helene C.; Jansen, Patrick A.; Wright, S. Joseph
Summary: Identification of the mechanisms enabling stable coexistence of species with similar resource requirements is a central challenge in ecology. Such coexistence can be facilitated by species at higher trophic levels through complex multi‐trophic interactions, a mechanism that could be compromised by ongoing defaunation. We investigated cascading effects of defaunation on Pachymerus cardo and Speciomerus giganteus, the specialized insect seed predators of the Neotropical palm Attalea butyracea, testing the hypothesis that vertebrate frugivores and granivores facilitate their coexistence. Laboratory experiments showed that the two seed parasitoid species differed strongly in their reproductive ecology. Pachymerus produced many small eggs that it deposited exclusively on the fruit exocarp (exterior). Speciomerus produced few large eggs that it deposited exclusively on the endocarp, which is normally exposed only after a vertebrate handles the fruit. When eggs of the two species were deposited on the same fruit, Pachymerus triumphed only when it had a long head start, and the loser always succumbed to intraguild predation. We collected field data on the fates of 6569 Attalea seeds across sites in central Panama with contrasting degrees of defaunation and wide variation in the abundance of vertebrate frugivores and granivores. Speciomerus dominated where vertebrate communities were intact, whereas Pachymerus dominated in defaunated sites. Variation in the relative abundance of Speciomerus across all 84 sampling sites was strongly positively related to the proportion of seeds attacked by rodents, an indicator of local vertebrate abundance. Synthesis . We show that two species of insect seed predators relying on the same host plant species are niche differentiated in their reproductive strategies such that one species has the advantage when fruits are handled promptly by vertebrates and the other when they are not. Defaunation disrupts this mediating influence of vertebrates and strongly favours one species at the expense of the other, providing a case study of the cascading effects of defaunation and its potential to disrupt coexistence of non‐target species, including the hyperdiverse phytophagous insects of tropical forests. Abstract : The unprecedented rates of defaunation, that is the loss of medium and large animals from ecosystems, are among the main features distinguishing the Anthropocene. With the fading of their populations, all their trophic interactions are also vanishing with unanticipated effects on the coexistence of other non‐target species.